Performance Improvement Management of Islamic Religious Education Supervisors at The Office of The Ministry of Religion, Binjai City - Yulinar, Yulinar; Nasution, Wahyuddin Nur; Siahaan, Amiruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The objectives of this research are: 1) To determine the planning for improving the performance of Islamic Religious Education supervisors at the Ministry of Religion of Binjai City, 2) To determine the organization of resources in improving the performance of Islamic Religious Education supervisors at the Ministry of Religion of Binjai City, 3) To determine the implementation of the supervisor performance improvement program Islamic Religious Education at the Ministry of Religion of Binjai City, and 4) To determine the supervision of improving the performance of Islamic Religious Education supervisors at the Ministry of Religion of Binjai City. This dissertation research uses a qualitative approach with descriptive methods because this research aims to obtain an overview of data originating from data collection by researchers regarding management of improving the quality of performance of Islamic Religious Education supervisors at the Ministry of Religion of Binjai City. Collection techniques use interview techniques, observation and document study, while to strengthen the validity of the data found and the authenticity of the research, the researcher refers to the use of data validity standards suggested by Lincoln & Guba, which consist of credibility, transferability, dependability and comfirmability.The results of this research are: 1) The plan to improve the performance of madrasa supervisors is carried out through a qualification improvement program, training, performance assessment and capacity development for Islamic Religious Education supervisors at the Ministry of Religion of Binjai City as well as the supervisory working group (Provincial/Regency/City Working Group). The initial efforts made to realize this program were preceded by building a mindset among madrasa supervisors with the aim of ensuring that supervisors know and understand their duties and functions, including preparing a supervision program in the form of coaching madrasa heads and teachers, monitoring the implementation of the 8 (eight) National Education Standards, Assessment , Teacher guidance and training as well as being an extension of the Ministry of Religion, 2) The organization carried out to improve the performance of madrasah supervisors is carried out as a team, however the aspect of coordination and synchronization in the implementation of activity programs between fields is not yet effective and needs to be improved, 3) The program to improve the performance of madrasah supervisors carried out through competency improvement training, capacity development, and performance assessment. However, the results have not been encouraging, especially in relation to the quality of supervisory coaching services which cover academic aspects for teachers in all subjects and managerial aspects of school principals which are felt to be less in line with the demands of expected performance standards and competencies, and 4) Supervision of improving the performance of Religious Education supervisors Islam in the Ministry of Religion of Binjai City is carried out jointly by involving various elements and working groups of provincial and district/city supervisors. This monitoring activity is intended to identify all forms of problems, find solutions and encourage improvements in the performance of supervisors.